IMPLEMENTASI PROGRAM KOMPREHENSIF BIMBINGAN DAN KONSELING DALAM PENGEMBANGAN POTENSI SISWA - Sri Damayanti (Universitas Muhammadiyah Tangerang, 2021)
Abstract:This type research was aims to determine the implementation of a comprehensive program of guidance and conseling in developing the potential of students at MTs Avicenna Sunan Bonang. This type of research is a qualitative descriptive study by collecting data about guidance and conseling services carried out by conseling guidance teachers in developing student potential. he result of this study indicates that study indicate that the implementation of a comprehensive program of guidance and conseling is appropriate in developing the potential of students at MTs Avicenna Sunan Bonang.